The journey from rhetoric to reality: participatory evaluation in a de velopment context - Chouinard, Jill Anne; Cousins, J. Bradley (Educational Assessment, Evaluation and Accountability, 2015)
In this paper, we focus on participatory evaluation in the context of international development and specifically on the emerging empirical k nowledge base. In a prior review and critique of research on participa tory evaluation (Cousins and Chouinard 2012), we examined 121 studies, with only 21 (17 %) situated in development contexts. However, the ci rcumstances and challenges for international development and for devel opment evaluation are distinct from those found in developed countries and therefore warrant separate consideration. To provide a more focus ed and detailed understanding of participatory evaluation in internati onal development contexts, in this paper we augment our initial sample to a total of 40 studies on participatory evaluation in development p ublished over the past 16.5 years. Based on an analysis of this resear ch and related theoretical and conceptual contributions we identify an d discuss eight emergent themes: multiplicity of relationships, conseq uences of stakeholder selection, characterization of participation, co ntextual complexity, methodological requirements, cultural influence, politics and power and learning and capacity building. We conclude wit h some reflections on an agenda for research.